Age, Pulse, Urea, and Albumin Score: A Tool for Predicting the Short-Term and Long-Term Outcomes of Community-Acquired Pneumonia Patients With Diabetes - Ma, Chun-Ming; Wang, Ning; Su, Quan-Wei; Yan, Ying; Wang, Si-Qiong; Ma, Cui-Hua; Liu, Xiao-Li; Dong, Shao-Chen; Lu, Na; Yin, Li-Yong; Yin, Fu-Zai (Frontiers in Endocrinology, 2022)
Objective: The predictive performances of CURB-65 and Pneumonia Severity Index(PSI) were poor in patients with diabetes. This study aimed to develop a tool for predicting the short-term and long-term outcomes of CAP in patients with diabetes. Methods: A retrospective study was conducted on 531 CAP patients with type 2 diabetes. The short-term outcome was in-hospital mortality. The long-term outcome was 24-month all-cause death. APUA score was calculated according to the levels of Age(0-2points), Pulse(0-2points), Urea(0-2points) and Albumin(0-4points). The area under curves(AUCs) were used to evaluate the abilities of APUA score for predicting short-term outcomes. Cox regression models were used for modeling relationships between APUA score and 24-month mortality. Results: The AUC of APUA score for predicting in-hospital mortality was 0.807 in patients with type 2 diabetes (P<0.001). The AUC of APUA score was higher than the AUCs of CURB-65 and PSI class (P<0.05). The long-term mortality increased with the risk stratification of APUA score(low risk group(0-1points) 11.5%, intermediate risk group(2-4points) 16.9%, high risk group(≥5points) 28.8%, P<0.05). Compared with patients in low risk group, patients in high risk group had significantly increased risk of long-term death, HR(95%CI) was 2.093(1.041～4.208, P=0.038). Conclusion: The APUA score is a simple and accurate tool for predicting short-term and long-term outcomes of CAP patients with diabetes.